(untitled) (Scholars’ Journal, 2021)
Demonetisation of Indian Currency of Rs 500 and Rs 1000 notes was taken as an important tool to fight against crime, tax evasion, corruption and other activities held in underground economy in India. Demonetisation in India directly affected the Nepali economy as India is the largest trading partner with common cultural relationship and open-border. The objective of the study was to examine the effect of recent demonetisation (November. 8, 2016) of India to Nepal. The study used the systematic review to find the effect of Indian demonetisation to the Nepali economy. The study found that it has paved the way for digital payments and supported the process of financial inclusion. The overall transformation in the economy translates into long-term benefit for the industry in India. But, the informal firms faced the liquidity crunch to pay their suppliers and workers without the standard access to cash in India. However, business sector and general people of Nepal are hard hit by the demonetisation because India is not making adjustments to take back demonetised IRs 500 and IRs 1000 notes estimated to be over Rs. 100 million, more than it the Indian policy departure has direct effect in Nepal. The demonetisation policy has created negative effect in Nepal to the greater extent from migrant labours to big business houses.